ANALISIS KARAKTER TOKOH UTAMA DALAM NOVEL “TO KILL A MOCKINGBIRD” KARYA HARPER LEE - Reni Puspitasari Sekarjadi; Udayani Permanaludin; Yoyo Thoyib (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to analyze the character and characterization of the main characters, focusing on how the writer presents them and how conflicts influence their development. The study employs relevant theories, particularly Sumardjo and Saini's theory of characterization (1988: 44) and Brooks and Warren's theory of plot (1959: 682). The research follows a descriptive method to explore the character and characterization of the main characters, with data gathered from dialogue exchanges, actions, stream of consciousness, responses from other characters, setting, and physical descriptions linked to the conflict. The findings demonstrate that the conflict leads to a transformation in the characterization of the main character, shifting from negative to positive traits. It is hoped that the results of this study will contribute to further research on character and characterization in novels, providing readers with a clearer understanding of character development. Keywords: Characterization, Conflict, Character Development.